Rare Birds of North America - Howell, Steve N. G.; Russell, Will (Ornithologist); Lewington, Ian (Book collections on Project MUSE., 2014)
A comprehensive, illustrated guide to the vagrant birds that occur throughout the United States and Canada. This book covers 262 species originating from three very different regions: the Old World, the New World tropics, and the world's oceans.